Personificación de Modelos de Elementos Finitos de Cuerpo Humano: Evaluación Cinemática - Piqueras Lorente, Ana; Iraeus, Johan; López Valdés, Francisco José; Lorente Corellanos, Ana Isabel; Juste Lorente, Óscar; Maza Frechín, Mario Vicente; Pipkorn, Bengt (Jornada de Jóvenes Investigadores del I3A, 2019)
The goal of this study was to quantify the effect of improving the geometry of a human body model on the accuracy of the predicted kinematics for 4 post-mortem human subject sled tests. Three modifications to the computational human body model THUMS were carried out to evaluate if subject personification can increase the agreement between predicted and measured kinematics of post-mortem human subjects in full frontal and nearside oblique impacts. The modifications consisted of: adjusting the human body model mass to the actual subject mass, morphing it to the actual anthropometry of each subject and finally adjustment of the model initial position to the measured position in selected post-mortem human subject tests.A quantitative assessment of the agreement between predicted and measured response was carried out by means of CORA analysis by comparing the displacement of selected anatomical landmarks (head CoG, T1 and T8 vertebre and H-Point).For all three scenarios, the more similar the human body model was to the anthropometry and posture of the sled tested post-mortem human subject, the more similar the predictions were to the measured responses of the post-mortem human subject, resulting in higher CORA score.